Prosecutorial Misconduct and Constitutional Remedies - Peter J. Henning (Washington University Law Quarterly, 1999)
This Article analyzes the Supreme Court’s determination of whether prosecutorial misconduct violated a defendant’s rights, as well as the related issue of what constitutional remedies are available to redress the prosecutor’s violation. The issues are connected because the Court frequently refers to prosecutorial intent as a facet of its misconduct analysis. The Article maintains that reliance on actual intent is misguided because it can elevate punishing a prosecutor to deter future misconduct above granting a constitutional remedy to correct harm to a defendant. Moreover, in the one instance in which the Court sanctions judicial inquiry into prosecutorial motives, the exercise of peremptory challenges, the result has been to create an impression of injustice. The Article concludes that, rather than misinterpreting constitutional protections to permit relief as a deterrent to future prosecutorial misconduct, courts should employ non-constitutional means to police the conduct of prosecutors.
Keywords: Prosecutorial misconduct; Remedies (Law); Constitutional law; Misconduct in office; Public prosecutors